Addressing information poverty in enhancing Small and Medium-scale Enterprisesfor economic growth in the Global South - Igbinovia, Magnus; Okuonghae, Omorodion; Akidi, Juliana; Ambrose, Smart Eromosele (Folia Toruniensia, 2025)
Background: The need for economic growth among the nations of the Global South has necessitated inquiries into Small and Medium-scale Enterprises (SMEs) as drivers of such growth. However, how well SMEs will function is determined by certain factors like information poverty, which places entrepreneurs as vulnerable users of business information. Purpose: The article explored factors that address information poverty toward enhancing SMEs for economic growth in the Global South.. Methodology: The study adopted a Rapid Literature Review (RLR) approach to synthesise literature on how addressing concepts of information poverty (information literacy, access to information and information infrastructure) would enhance SMEs in the nations of the Global South. EBSCOhost, ProQuest, and Google Scholar were used for the review, which hinged on four eligibility criteria: methodology, publication year, language and publication source. Findings: The study found that information literacy positions entrepreneurs with the right skills to grow their enterprises in the information-driven economy, impacting their business performances. The analyses also showed that access to required information predicts entrepreneurs’ business growth and sustainability. Moreover, the study found information infrastructure as an essential asset in improving the competitiveness of SME owners leading to their business growth. These three factors (information literacy, access to information and information infrastructure) were found to be crucial in addressing information poverty toward the growth of SMEs. Conclusion: The study concluded that when entrepreneurs possess information literacy, and have unhindered access to information and information infrastructures, there will be a better performance in their enterprises, which will in turn impact the economic growth of nations in the Global South.